A LATERAL APPROACH TO ETHICS IN BUSINESS - Piskrzyńska, Katarzyna; Cieślar, Szymon (International Journal of Economics, Business, and Entrepreneurship, 2018)
Ethical issues in enterprises are often discussed in the scientific studies. Most of them describe organizational ethics from the perspective of corporate social responsibility or its impact on the behavior of employees in the organization. The authors decided to depart from the schematic formulaic thinking of ethics as a set of normative values for a purely business approach. Looking for opportunities to use organizational ethics in promotional activities or when determining the value of goods and services. The aim of this article is to present selected approaches to ethical issues in the organization and to present the results of authors’ our research. The Authors in their study use research methods such as literary research and primary research using the survey tool. Surveys were conducted in Poland in the period from January 2017 to October 2017 and they included a random sample of respondents. The main hypothesis was also formulated: H0: Ethics in the enterprise can be purely binary, For the purpose of the study, the following hypotheses were formulated: H1: Ethics can be used to shape prices H2: Ethics affects consumers' decisions H3: Unethical behaviors in the enterprise worsen its competitiveness, In addition, this publication underlines individual moral considerations of the ethical aspects of using ethics in the enterprise to increase profits and thereby create a paradox of unethical use of ethics.